2020
DOI: 10.3390/antibiotics9100672
|View full text |Cite
|
Sign up to set email alerts
|

Is Early Monitoring Better? Impact of Early Vancomycin Exposure on Treatment Outcomes and Nephrotoxicity in Patients with Methicillin-Resistant Staphylococcus aureus Infections

Abstract: Optimal early vancomycin target exposure remains controversial. To clarify the therapeutic exposure range, we investigated the association between vancomycin exposure and treatment outcomes or nephrotoxicity in patients with methicillin-resistant Staphylococcus aureus (MRSA) infection. This retrospective study reviewed clinical data obtained from 131 patients with MRSA infections between January 2017 and September 2019. Clinical outcomes included treatment failure, 30-day mortality, microbiological failure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
(44 reference statements)
0
14
0
Order By: Relevance
“…However, our study did not evaluate treatment efficacy against MSRA infections and nephrotoxicity according to the estimated vancomycin AUC during the first day [ 20 ]. The clinical benefit of the vancomycin AUC based on Bayesian estimation for MRSA treatment in the first day must be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study did not evaluate treatment efficacy against MSRA infections and nephrotoxicity according to the estimated vancomycin AUC during the first day [ 20 ]. The clinical benefit of the vancomycin AUC based on Bayesian estimation for MRSA treatment in the first day must be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the AUC thresholds for nephrotoxicity are varied, but more previous evidence showed that nephrotoxicity increased in patients with AUC > 600 mg·h/L. 10 , 11 , 12 , 13 , 14 , 15 , 16 A meta‐analysis reported that the incidence of AKI in AUC‐guided monitoring was lower than in trough‐guided monitoring (OR 0.54, 95% CI 0.28–1.01). 17 Implement AUC‐based dosing protocol using two concentrations can improve the therapeutic vancomycin target and reduce nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…AUC 24 was calculated using the Bayesian method with the APK© software (version 3.5.28, RxKinetics, Plattsburg, MO). As previous studies suggested that the vancomycin AUC/MIC be optimized early in the course of infection [17][18][19], AUC 24 /MIC and C trough during the initial 72 h of treatment were chosen as measures of drug exposure. The average AUC 24 /MIC and C trough values during the initial 72 h were calculated as arithmetic means.…”
Section: Microbiologic and Pharmacokinetic/pharmacodynamic Analysismentioning
confidence: 99%